Resolusi Konflik Berbasis Teologi Baku Bae Ambon (1999-2002) - Burhanuddin Tidore (Media: Jurnal Filsafat dan Teologi, 2022)
This paper aims to discuss the pattern of resolution of the Ambon conflict that occurred in 1999-2002 and was caused by various complex factors. This study offers a conflict resolution approach using the so-called BakuBae theology, which is based on religious values and local wisdom. In this qualitative research, the author deals with the theme from the perspectives of theology, history, and culture, and uses convergence as the theme point. This study found that the dynamics of the Ambon conflict had a multi-dimensional background (political, economic, social, and cultural). The pattern of conflict resolution using a top-down approach to the security aspect, namely the role of the TNI-Polri institutions, which tend to be repressive, has caused the division of social and religious identities between Salam-Sarane (Islam-Christian) in Ambon. This actually complicates the process of ending the conflict. On the other hand, the bottom-up approach of the BakuBae social movement has involved civil society and grassroots groups that play a significant role in conflict resolution. The program of BakuBae has become the right pattern for conflict resolution. The findings of BakuBae's work are the key to a solution to the conflict in Ambon.